The impact of shift work on the psychological and physical health of nurses in a general hospital: a comparison between rotating night shifts and day shifts - Ferri P; Guadi M; Marcheselli L; Balduzzi S; Magnani D; Di Lorenzo R (Dove Medical Press, 2016)
Paola Ferri,1 Matteo Guadi,1 Luigi Marcheselli,1 Sara Balduzzi,1 Daniela Magnani,1 Rosaria Di Lorenzo2 1Department of Diagnostic, Clinical and Public Health Medicine, University of Modena and Reggio Emilia, 2Department of Mental Health, AUSL di Modena, Service of Psychiatric Diagnosis and Treatment, Modena, Italy Background: Shift work is considered necessary to ensure continuity of care in hospitals and residential facilities. In particular, the night shift is one of the most frequent reasons for the disruption of circadian rhythms, causing significant alterations of sleep and biological functions that can affect physical and psychological well-being and negatively impact work performance.Objectives: The aim of this study was to highlight if shift work with nights, as compared with day work only, is associated with risk factors predisposing nurses to poorer health conditions and lower job satisfaction.Methods: This cross-sectional study was conducted from June 1, 2015 to July 31, 2015 in 17 wards of a general hospital and a residential facility of a northern Italian city. This study involved 213 nurses working in rotating night shifts and 65 in day shifts. The instrument used for data collection was the “Standard Shift Work Index,” validated in Italian. Data were statistically analyzed.Results: The response rate was 86%. The nurses engaged in rotating night shifts were statistically significantly younger, more frequently single, and had Bachelors and Masters degrees in nursing. They reported the lowest mean score in the items of job satisfaction, quality and quantity of sleep, with more frequent chronic fatigue, psychological, and cardiovascular symptoms in comparison with the day shift workers, in a statistically significant way.Conclusion: Our results suggest that nurses with rotating night schedule need special attention due to the higher risk for both job dissatisfaction and undesirable health effects. Keywords: shift work, night work, health, sleep disorders, job satisfaction, nurses